Evaluation of influenza vaccination efficacy in reducing influenza-related complications and excess mortality in Northern Italy (2014-2017). (2nd January 2021) - Marano, Giuseppe; Boracchi, Patrizia; Luconi, Ester; Pariani, Elena; Pellegrinelli, Laura; Galli, Cristina; Gandolfi, Cecilia E.; Magoni, Michele; Piro, Antonio; Scarcella, Carmelo; Castaldi, Silvana; Biganzoli, Elia M.
ABSTRACT: Objective: The main objective of this study was to estimate the efficacy of influenza vaccination in reducing influenza-attributable hospitalization and emergency room (ER) admission for severe complications and influenza-attributable excess mortality in individuals ≥65 years of age. Methods: We analyzed the ≥65 years-old community (n = 952, 822) afferent to the Brescia (Northern Italy) Health Protection Agency, considered an Italian population reference, to evaluate the efficacy of influenza vaccination (seasons 2014–17) in reducing deaths, ER-admissions, and hospitalizations for influenza-related complications in the elderly. Results: A protective effect of influenza vaccination emerged in reducing hospitalization and ER admission for diseases of the respiratory system and for death from all causes in people ≥65 years. The major effect of influenza vaccination was the reduction in risk of death from all causes, increasing with age and comorbidity. Conclusion: Influenza vaccination has reduced the number of ER admissions and hospitalizations caused by influenza-related complications and has prevented death among high-risk groups in elderly ≥65 years, resulting in social and public health cost savings. Stronger or new vaccination strategies are needed to improve vaccination rates among the elderly.